2014
DOI: 10.1017/s0140525x13002380
|View full text |Cite
|
Sign up to set email alerts
|

The origin and function of mirror neurons: The missing link

Abstract: We argue, by analogy to the neural organization of the object recognition system, that demonstration of modulation of mirror neurons by associative learning does not imply absence of genetic adaptation. Innate connectivity defines the types of processes mirror neurons can participate in while allowing for extensive local plasticity. However, the proper function of these neurons remains to be worked out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 381 publications
0
2
0
Order By: Relevance
“…How human and nonhuman studies on motor cognition may be compared, and how direct (in monkeys) and indirect (in humans) evidence may mutually support the idea of motor-based understanding has been matter of debate. Thus, also alternative and competitive explanations questioning the motor approach to cognition have been proposed (Caramazza and others 2014; R Cook and others 2014; Hickok 2009; Lingnau and Caramazza 2014). However, and beyond competitive explanations, taken together these findings seem robust in indicating that mirror mechanism is not specific feature of the premotor cortex, but it should be considered a basic principle of brain functioning (Rizzolatti and Sinigaglia 2016).…”
Section: Non-motor Functions Of the Motor System: Clinical Implicatiomentioning
confidence: 99%
“…How human and nonhuman studies on motor cognition may be compared, and how direct (in monkeys) and indirect (in humans) evidence may mutually support the idea of motor-based understanding has been matter of debate. Thus, also alternative and competitive explanations questioning the motor approach to cognition have been proposed (Caramazza and others 2014; R Cook and others 2014; Hickok 2009; Lingnau and Caramazza 2014). However, and beyond competitive explanations, taken together these findings seem robust in indicating that mirror mechanism is not specific feature of the premotor cortex, but it should be considered a basic principle of brain functioning (Rizzolatti and Sinigaglia 2016).…”
Section: Non-motor Functions Of the Motor System: Clinical Implicatiomentioning
confidence: 99%
“…Recently, studies in Neuroscience have shown that repetition is also related to mirror neurons, one of Neuroscience's most important discoveries to date. Mirror neurons are known as the imitating cells in human brain that are believed to play a role in language acquisition, and other forms of imitative behavioural learning (Lingnau & Caramazza, 2014).…”
Section: Chapter: Syntactic Primingmentioning
confidence: 99%